Health risks evaluation of mycotoxins in plant-based supplements marketed in Malaysia - Abdullah, Rozaini; Kamarozaman, Nur Syazwin; Ab Dullah, Siti Soleha; Aziz, Mohd Yusmaidie; Aziza, Hussein Bakheit Adam (Nature Research, 2025)
Mycotoxins are toxic secondary metabolites produced by fungi, pose significant health risks when present in plant-based supplements (PBS), necessitating thorough risk assessment to ensure consumer safety. This study evaluates the health risks associated with mycotoxins, specifically aflatoxins (AFB1, AFB2) and ochratoxin A (OTA), in PBS sold in Malaysia. Contamination levels of AFB1, AFB2, and OTA were quantified in 14 PBS samples using Liquid Chromatography-Mass Spectrometry. All samples tested positive for AFB2, while 28.57% and 42.86% tested positive for AFB1 and OTA, respectively with some levels exceeding the regulatory limits set by the Malaysian Food Act 1983 and European regulations. The estimated daily intake of these mycotoxins was calculated based on the recommended daily intake of each supplement. To assess risk, Margin of Exposure (MOE) values were determined, showing that all AFB2-positive samples had MOE values below the critical threshold of 10,000, indicating an urgent need for risk management. A quantitative cancer risk assessment also estimated the percentage of hepatocellular carcinoma and kidney cancer attributable to mycotoxin exposure. The findings emphasize the significant public health risks posed by mycotoxins, particularly in samples B2 and B10, where all three mycotoxins studied were present at concerning levels. This study highlights the urgent need for stricter regulations and better monitoring of mycotoxin levels in PBS to protect consumer’s health.